Recent Patents and Advances in Regenerative Medicine and Stem Cell Therapies for Diabetes, Cardiovascular and Neurodegenerative Diseases - I. Saad, Mohamed; A. Kamel, Maher; M. Abdelkhalek, Taha; M. Saleh, Moustafa; H. Tawfik, Shady (Recent Patents on Regenerative Medicine, 2015)
In recent years, cell-based therapies have gained great enthusiasm as a new therapeutic approach for addressing many disorders. Many researchers have shown the roles of stem cells in replacing damaged tissues and in providing extracellular factors that can promote endogenous cellular replenishment. Also, stem cells are rich source of soluble factors and microvesicles, which are released from their surfaces and thereby exerting paracrine effect. Although pluripotent stem cells are considered the cornerstone in regenerative medicine, various types of more differentiated adult stem and progenitor cells are exploited. In this review, we provide an overview about the recent advances in the field of regenerative medicine and stem cell therapies for diabetes, cardiovascular and neurodegenerative diseases, with special interest in the recent patents. Patents from WIPO, USPTO, Patent scope and European patent databases have been discussed. In conclusion, the increasing number of patents and the extensive scientific research suggests that stem cell therapies hold a promising future for the management of incurable diseases.
Keywords: neurodegenerative disorders